2022
DOI: 10.3390/healthcare10122513
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Knowledge, Attitude, and Practice of Medication Therapy Management: A Systematic Review

Abstract: Understanding pharmacists’ knowledge, attitudes, and practices (KAP) and their perceptions of challenges, barriers, and facilitators towards medication therapy management (MTM) provision are vital in informing the design and implementation of successful service delivery. Thus, this review examined pharmacists’ knowledge, attitudes, and practices, and their perceived challenges, barriers, and facilitators to MTM services provision, globally. A systematic search was conducted on 1–31 August 2022 to identify rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
(296 reference statements)
3
6
0
Order By: Relevance
“…Studies have shown the positive effect of this pilot project of MTM on clinical and humanistic outcomes ( 6 8 ). These findings are consistent with those of many studies that have demonstrated the benefits of MTM on clinical, economic, and humanistic outcomes in other countries ( 5 , 10 ).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Studies have shown the positive effect of this pilot project of MTM on clinical and humanistic outcomes ( 6 8 ). These findings are consistent with those of many studies that have demonstrated the benefits of MTM on clinical, economic, and humanistic outcomes in other countries ( 5 , 10 ).…”
Section: Introductionsupporting
confidence: 92%
“…Generally, the health facility/organization factor became the main barrier for pharmacists. Pharmacists in the studies in other countries perceived similar barriers to MTM, including the lack of time, staffing, compensation, and training ( 10 ). Fewer identified facilitators indicated that pharmacists appeared to emphasize barriers and overlook facilitators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar medication management strategies have also been adopted in other nations, including the UK's Medication Use Review (MUR), Australia's Quality Use of Medicine (QUM), and Residential Medication Management Review (RMMR) [16,17]. However, the USA MTM approach has been accepted for use in many nations [18,17]. According to a 2004 survey conducted in the United States, just about 17% of pharmacies provided disease-state management services, and only 10% of pharmacists provided MTM services [19].…”
Section: Introductionmentioning
confidence: 99%